Segmentasi Wisatawan Agrowisata Berbasis Padi Sawah Di Kabupaten Deli Serdang: Systematic Literature Review - Pradana, Dendi; Ilvira, Rika Fitri (Jurnal Ilmiah Pertanian ( JIPERTA), 2025)
This study aims to identify and analyze the segmentation of agro-tourism tourists based on paddy fields in Deli Serdang Regency. The method used was a systematic literature review by analyzing 32 scientific articles indexed by Scopus and Sinta in the period 2015-2024. The results showed that the segmentation of wet-rice agro-tourism tourists can be divided based on four main factors: demographic, geographic, psychographic, and behavioral. Based on visit motivation, tourists can be segmented into educational seekers, recreational seekers, authenticity seekers, and social media enthusiasts. Based on behavior, tourists are divided into visitors with short, medium, and long visit durations, and based on transportation mode (private vehicle, public transportation, and organized tour). This research provides implications for the development of marketing strategies and management of agro-tourism based on paddy fields in Deli Serdang Regency that are more focused according to the characteristics of the tourist segment, to increase the competitiveness and sustainability of agro-tourism destinations.